Particle Size Improvement and Layer Absorption of Metil Halida MAPbI3 Perovskite Doping Phenethylammonium Iodide (PEAI) - Anla, Anla Fet Hardi; Dahyunir, Dahyunir; muldarisnur, muldarisnur; Amrullah, Yasir; Sadikin, Siti Naqiyah; Ridwan, Jaenudin; Umar, Akrajas Ali (Jurusan Fisika FMIPA Universitas Andalas, 2024)
This study aims to determine the effect of phenethylammonium iodide (PEAI) doping on grain size and absorption of the methylammonium lead iodide (MAPbI3) perovskite layer. The MAPbI3 perovskite layer is interesting to study because of its potential application in perovskite solar cells. In this study, the preparation of MAPbI3 perovskite layer with PEAI doping variation using a 2-step spin-coating method. The surface morphology of MAPbI3 shows an increase in grain size with the addition of PEAI doping variation. The optimum grain size is shown by adding 1.0 mg/ml PEAI doping variation, which is 117 ± 1.19 nm with a smooth surface morphology and tends to be homogeneous. X-ray diffraction (XRD) results on Perovskite MAPbI3 showed no difference in peaks with the addition of PEAI doping. However, there is only a slight angle shift of 2 theta, 0.05° at the main peak (110) and (220), so it will not change the cubic structure of MAPbI3 crystal. The ultra violet visible (UV-Vis) graph shows an increase in absorbance of Perovskite MAPbI3 with the addition of PEAI doping in the wavelength range of 400-550 nm. This research is expected to be a foundation for developing more efficient and stable solar cells.